Neoadjuvant bevacizumab and chemoradiotherapy in locally advanced rectal cancer: early outcome and technical impact on toxicity - Wang, Chia-Chun (World J Surg Oncol, 2014)
BACKGROUND: We aimed to evaluate early clinical and pathological results for treating locally advanced rectal cancer with bevacizumab and neoadjuvant concurrent chemoradiotherapy using the technique of prone-position volumetric modulated arc therapy and to compare the toxicity of volumetric modulated arc therapy with that of supine-position four-field box radiotherapy. METHODS: Twelve patients with stage IIA to IVA rectal adenocarcinoma, treated with neoadjuvant concurrent chemoradiotherapy (45 Gy in 25 fractions to the rectal tumor and pelvic lymphatics) and bevacizumab, were prospectively enrolled. Chemotherapy included FOLFOX (leucovorin, fluorouracil, and oxaliplatin) (n =11) and 5-fluorouracil (n =1). All patients received prone-position volumetric modulated arc therapy. A historical cohort treated with supine-position box radiotherapy, including six other patients treated with bevacizumab-based concurrent chemoradiotherapy in our hospital, was used for comparison. Setup errors, toxicities, and potential biomarkers were evaluated. RESULTS: All patients completed neoadjuvant concurrent chemoradiotherapy and underwent total mesorectal excision. Four (33.3%) patients had pathological complete response. Significantly more grade 2 or 3 diarrhea was associated with the supine-box technique (5/6 versus 2/12, P =0.01). The magnitude of setup errors was similar between the supine-box and prone volumetric modulated arc therapy techniques. The estimated 2-year survival and 2-year failure-free survival rates were 100% and 72.9% in the prone volumetric modulated arc therapy group and 66.7% and 66.7% in the supine box group, respectively. CONCLUSIONS: The early clinical outcome has been encouraging. Volumetric modulated arc therapy in prone-positioned patients was technically advantageous and reduced bowel toxicity.